Health care utilization and mortality associated with heart failure‐related admissions among cancer patients. (2nd July 2019) - Guha, Avirup; Dey, Amit Kumar; Armanious, Merna; Dodd, Katherine; Bonsu, Janice; Jneid, Hani; Abraham, William; Fradley, Michael G.; Addison, Daniel
Abstract: Aims: Heart failure (HF) outcomes continue to improve with widespread use of new therapies. Concurrently, cancer survival has dramatically improved. Yet whether cancer patients share similar strategies and outcomes of inpatient HF treatment to those without HF is unknown. We sought to assess the contemporary impacts of cancer on inpatient HF outcomes over time. Methods and results: The retrospective National Inpatient Sample (2003–15) and National Readmissions Database (2013–14) registries were queried for adults admitted for HF and stratified for cancer status, excluding cases of metastatic disease. Temporal trends in HF admissions, hospital charge rates, length of hospitalization, HF‐related procedure utilization, in‐hospital mortality, and hospital readmissions were analysed. Over 13 years of follow‐up, there were 12 769 077 HF admissions (mean age 73 years, 50.8% female, 30.8% non‐White), among which 1 413 287 (11%) had a co‐morbid cancer diagnosis. Cancer patients were older, were predominantly male, and tended to be smokers. Over time, HF admission rates among cancer patients increased, despite a concurrent decrease among patients without cancer ( P < 0.0001). After propensity matching, in‐hospital mortality was significantly higher among cancer HF patients (5.1% vs. 2.9%, P < 0.0001). Additionally, HF‐related procedure utilization was disproportionately lower among cancer patients (0.30 vs. 0.35 procedures/HF hospitalization, P < 0.001); the presence of cancer was associated with increased costs, length of hospitalizations, and all‐cause readmissions, but fewer HF readmissions ( P < 0.0001, each). Conclusions: While the incidence of HF hospitalizations has increased among cancer patients, they do not appear to share the same rates of advanced HF care, readmissions trends, or reductions in in‐hospital mortality. Future studies targeting modifiable factors related to these differences are needed.